The Essential Norm of the Generalized Hankel Operators on the Bergman Space of the Unit Ball in Cn - Luo Luo; Yang Xuemei (Abstract and Applied Analysis)
In 1993, Peloso introduced a kind of operators on the Bergman space A2(B) of the unit ball that generalizes the classical Hankel operator. In this paper, we estimate the essential norm of the generalized Hankel operators on the Bergman space Ap(B)  (p>1) of the unit ball and give an equivalent form of the essential norm.